System Development for Learning Process Monitoring in Private Lesson Institution Using Codeigniter Framework - Herdiansah, Arief (JISA(Jurnal Informatika dan Sains), 2021)
The monitoring information system is one of the main functions in managing student data in Generasi Cerdas private lesson. This study provides the results of an analysis and design of a monitoring information system that can be used to facilitate services to students in monitoring including grades and student absence. This application developed using UML Design and PHP Programming with CodeIgniter Framework and use MySQL Database. CodeIgniter is an open source framework in the form of a PHP framework with an MVC model (Model, View, Controller) for building dynamic websites. The resulting application has been able to provide information of teacher, student, student value and student absence data to assist in processing student and teacher data in the Generasi Cerdas private lesson, so that the institution has a faster, more efficient monitoring information system and easier to use.